Milk emission curves in different parities in Italian Brown Swiss cattle - D. Vigo; C. Maltecca; A. Rossoni; A. Bagnato; S. Ghiroldi (Italian Journal of Animal Science, 2011)
In modern dairy farm practice functional traits hold an increasing importance (Groen, 1997) and many population selection programs include traits related with milkability (Soelkner, 2002). Milkability affect farmer’s net profit (Sivarajasingam et al., 1984) and is one of the functional traits that affect involuntary culling (Frerking, 1999). Usually milkability is measured as milking speed, either recorded as slow, average, or fast, or as time in seconds from the seating of the teat cups until their removal. Since 1992, in the Italian Brown population, milking performance is recorded with electronic flowmeters and genetic evaluations of individuals are available for average milk flow. The flowmeter technology allows to collect information concerning the shape of milk releasing curves and to use it to implement a genetic selection program. A previous study showed heritability of 0.21 for maximum milk flow and 0.14 for time at stable flow with a genetic correlation between them of -0.65, values that suggest the possibility for selection on milking parameters (Santus and Bagnato 1998). Objective of this study is the investigation of variation of parameters describing the milking emission curves along the animal career and to address relationship between curve shapes with production and somatic cell count.